2008
DOI: 10.1039/b703021p
|View full text |Cite
|
Sign up to set email alerts
|

Expanding dialogues: from natural autoinducers to non-natural analogues that modulate quorum sensing in Gram-negative bacteria

Abstract: Bacteria are capable of "communicating" their local population densities via a process termed quorum sensing (QS). Gram-negative bacteria use N-acylated l-homoserine lactones (AHLs), in conjunction with their cognate LuxR-type receptors, as their primary signalling circuit for QS. In this critical review, we examine AHL signalling in Gram-negative bacteria with a primary focus on the design of non-natural AHLs, their structure-activity relationships, and their application in chemical biological approaches to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
267
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 219 publications
(273 citation statements)
references
References 76 publications
4
267
0
2
Order By: Relevance
“…Analogues have been found that exhibit a range of different activities, including no activity, pure agonism or pure antagonism, partial agonism, and synergistic agonism (167,(170)(171)(172). The different AHL analogues tested to date and their specific activities against the various receptor proteins are too numerous to report here in detail, so for a more comprehensive and specific discussion of these molecules we refer the reader to other recently published reviews (173,174). There are some general findings of these investigations, however, that we have chosen to discuss below, as well as several specific examples of AHL receptor antagonists that show promise for the future development of analogue-based QSI strategies.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…Analogues have been found that exhibit a range of different activities, including no activity, pure agonism or pure antagonism, partial agonism, and synergistic agonism (167,(170)(171)(172). The different AHL analogues tested to date and their specific activities against the various receptor proteins are too numerous to report here in detail, so for a more comprehensive and specific discussion of these molecules we refer the reader to other recently published reviews (173,174). There are some general findings of these investigations, however, that we have chosen to discuss below, as well as several specific examples of AHL receptor antagonists that show promise for the future development of analogue-based QSI strategies.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…Bacteria colonizing or infecting a host grow under hostile conditions, sense changing environmental stress via diverse quorum sensing, and other two-component systems, and respond by up-or downregulating the expression levels of appropriate proteins, which in turn can affect the susceptibility of the cell to antibiotics (2,11). Examples of environmental stress include, e.g., growth at extreme temperatures, pH, osmotic pressure, and depletion of nutrients, etc.…”
mentioning
confidence: 99%
“…The linkage between QS and the production of virulence factors in P. aeruginosa predicts that inhibition of AHL-mediated gene expression could render these bacteria nonpathogenic (5). Studies on the rational design of QS inhibitors have focused on modifying the basic structure of the AHL (4,9). High-throughput screening (HTS) of smallmolecule libraries is another approach for the identification of compounds that have novel chemical scaffolds for both the development of chemical probes and eventual therapeutic drug design.…”
mentioning
confidence: 99%